2021
DOI: 10.1007/s00066-021-01884-0
|View full text |Cite
|
Sign up to set email alerts
|

Chasing a rarity: a retrospective single-center evaluation of prognostic factors in primary gliosarcoma

Abstract: Background and purpose Primary gliosarcoma (GS) is a rare variant of IDH-wildtype glioblastoma multiforme. We performed a single-center analysis to identify prognostic factors. Patients and methods We analyzed the records of 26 patients newly diagnosed with primary WHO grade IV GS. Factors of interest were clinical and treatment data, as well as molecular markers, time to recurrence, and time to death. Results Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
1
1
Order By: Relevance
“…The situation is generally consistent with the previous research results [17][18][19][20][21][22]. In our cohort, the proportion of patients with secondary GSM is 17.8%, which is still consistent with existing reports [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…The situation is generally consistent with the previous research results [17][18][19][20][21][22]. In our cohort, the proportion of patients with secondary GSM is 17.8%, which is still consistent with existing reports [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…The median OS in our study was 25.6 months and longer than those in most other studies, which range from 5.7 months to 24.7 months [ 24 , 25 ]. The results of our study suggested that total resection of GSM was associated with prolonged OS and RFS.…”
Section: Discussioncontrasting
confidence: 62%
“…The results of our study suggested that total resection of GSM was associated with prolonged OS and RFS. Although some retrospective studies have reached the opposite conclusions [ 9 , 11 , 24 ], the resection range is a well-accepted independent prognostic factor for improved OS in GSM [ 4 , 5 , 17 , 26 , 27 ]. Cachia et al reported that patients of primary GSM undergoing GTR tended to have a greater OS (median 24.7 months) than those having subtotal resection (median 10.1 months) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%